∫ 0 1 ln ( 1 − x + 1 + x ) d x = A 1 ln ( B ) − C 1 + D π
If A , B , C , D are positive integers, where B is not a perfect power, evaluate A + B + C + D .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Wow great approach..!!
integration by parts was easier. But ya yours is a nice approach.
L e t x = sin 2 θ f o r θ ∈ ( 0 , 4 π ) ⇒ 1 − x = ∣ sin θ − cos θ ∣ = cos θ − sin θ f o r θ ∈ ( 0 , 4 π ) s i m i l a r i l y , 1 + x = cos θ + sin θ ⇒ 1 − x + 1 + x = 2 cos θ d x = 2 cos 2 θ d θ ∴ I = ∫ 0 1 ln ( 1 − x + 1 + x ) d x = ∫ 0 4 π ln ( 2 cos θ ) . 2 cos 2 θ d θ b y p a r t s , ∫ ln ( 2 cos θ ) . 2 cos 2 θ d θ = sin 2 θ . ln ( 2 cos θ ) − ∫ sin 2 θ 2 cos θ − 2 sin θ d θ = sin 2 θ . ln ( 2 cos θ ) + ∫ 2 sin 2 θ d θ = sin 2 θ . ln ( 2 cos θ ) − 2 1 sin 2 θ + θ + C ∴ ∫ 0 4 π ln ( 2 cos θ ) . 2 cos 2 θ d θ = [ sin 2 θ . ln ( 2 cos θ ) − 2 1 sin 2 θ + θ ] 0 4 π = 2 1 ln 2 − 2 1 + 4 π ∴ A + B + C + D = 2 + 2 + 2 + 4 = 1 0
Just try using normal integration by parts without substitution to get a simple and elegant solution!!
Problem Loading...
Note Loading...
Set Loading...
We start by using the logarithmic identity lo g b ( x d ) = d lo g b ( x ) . Using this, we can write the integrand as 2 1 ln ( 1 − x + 1 + x ) 2 . Thus, the integral becomes
I = ∫ 0 1 ln ( 1 − x + 1 + x ) d x = ∫ 0 1 2 1 ln ( 1 − x + 1 + x ) 2 d x = ∫ 0 1 2 1 ln ( ( 1 − x ) + 2 ( 1 − x ) ( 1 + x ) + ( 1 − x ) ) d x = ∫ 0 1 2 1 ln ( 2 + 2 1 − x 2 ) d x
From here, we make the substitution x = sin θ :
I = ∫ 0 1 2 1 ln ( 2 + 2 1 − x 2 ) d x = ∫ 0 π / 2 2 1 ln ( 2 + 2 1 − sin 2 θ ) ( c o s θ d θ ) = ∫ 0 π / 2 2 1 ln ( 2 + 2 cos θ ) c o s θ d θ
Now, we use integration by parts, such that
u d u = ln ( 2 + 2 cos θ ) = 2 + 2 cos θ − 2 sin θ d θ d v v = cos θ d θ = sin θ
Then, the value of the integral becomes
I = ∫ 0 π / 2 2 1 ln ( 2 + 2 cos θ ) c o s θ d θ = 2 1 ( ( ln ( 2 + 2 cos θ ) sin θ ) ∣ 0 π / 2 − ∫ 0 π / 2 2 + 2 cos θ − 2 sin 2 θ d θ ) = 2 1 ( ln ( 2 ) + ∫ 0 π / 2 1 + cos θ sin 2 θ d θ )
The resulting integral on the right can be simplified using the trigonometric identity sin 2 θ + cos 2 θ = 1 . Substituting 1 − cos 2 θ for sin 2 θ , we see that
∫ 0 π / 2 1 + cos θ sin 2 θ d θ = ∫ 0 π / 2 1 + cos θ 1 − cos 2 θ d θ = ∫ 0 π / 2 1 + cos θ ( 1 − cos θ ) ( 1 + cos θ ) d θ = ∫ 0 π / 2 ( 1 − cos θ ) d θ = ∫ 0 π / 2 1 d θ − ∫ 0 π / 2 cos θ d θ = 2 π − 1
Thus, the value of the integral is
I = 2 1 ( ln ( 2 ) + ∫ 0 π / 2 1 + cos θ sin 2 θ d θ ) = 2 1 ( ln ( 2 ) − 1 + 2 π ) = 2 1 ln ( 2 ) − 2 1 + 4 π
And therefore,
A + B + C + D = 2 + 2 + 2 + 4 = 1 0